Isolation and characterization of an archaebacterial viruslike particle from Methanococcus voltae A3. - Wood, A G (1989)
Small amounts of a 23-kilobase covalently closed circular DNA molecule were isolated from unwashed cells of Methanococcus voltae A3. Further investigation indicated the presence of greater quantities of the circular DNA in the culture supernatant, complexed with protein in a manner rendering the DNA resistant to DNase. Electron-microscopic examination of supernatant material revealed the presence of particles which morphologically resemble virus. Phenol extraction of viruslike particle preparations resulted in the recovery of DNase-sensitive open-circular DNA molecules. As many as 30 viruslike particles per cell were recovered from some cultures. Hybridization data clearly indicated the presence of a chromosomally integrated copy of the viruslike particle DNA. Although M. voltae PS was not observed to produce viruslike particles, DNA homologous to the viruslike particle DNA was detected in its chromosome. A mutant of M. voltae A3 was isolated which produced no particles; its DNA was deleted for 80% of the integrated viruslike particle DNA. Despite any similarities to lysogenic bacteriophages of eubacteria, neither infectivity nor inducibility of the viruslike particles could be demonstrated.